PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUTOPLAY MEDIA STUDIO 8.5 PADA POKOK BAHASAN IKATAN KIMIA UNTUK KELAS X SMA/MA - Anggraini, Dewi; Holiwarni, Betty; Abdullah, Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research of development of learning media based on AutoplayMedia Studio 8.5 is aimed to study the valid and practical learning media on the subjectof chemical bond. This research method is research development (Research andDevelopment, R & D) with 4-D development model covering define phase, Design,Develop and Disseminate. Instrument of data collection used through validation sheetand respondent questionnaire. Data analysis technique is by calculating the percentagescore of validation and user response. The results showed that the media based onAutoplay Media Studio 8.5 developed developed valid criteria of visual communication,instructional design, content, and ease of use with 93.98% score. Learning media alsomeet the practical criteria, which teachers and learners can use it in chemistry learningwith a score of 96.67% and 92%.Key Words : Learning Media, Autoplay Media Studio 8.5, Chemical Bond